Synthesis and characterization of barbarin, a possible source of unexplained aminorex identifications in forensic science. Issue 10 (26th August 2020) - Machin, Jacob; Childers, Taylor; Kudrimoti, Sucheta; Eisenberg, Rod; Fenger, Clara; Hartmann, Petra; Maylin, George; Shults, Theodore; Tobin, Thomas
Abstract: Aminorex is a US DEA Schedule 1 controlled substance occasionally detected in racing horses. A number of aminorex identifications in sport horses were thought to have been caused by exposure to plant sources of aminorex. Glucobarbarin, found in plants of the Brassicaceae family, has been suggested as a potential proximate chemical source by being metabolized in the plant or the horse to aminorex. In Brassicaceae, glucobarbarin is hydrolyzed by myrosinase to yield barbarin, which serves as an insect repellant and/or attractant and is structurally related to aminorex. The synthesis, purification, and characterization of barbarin is now reported for use as a reference standard in aminorex related research concerning equine urinary identifications of aminorex and also for possible use in equine administration experiments. Synthesis of barbarin was performed via ring closure between phenylethanolamine and carbon disulfide in tetrahydrofuran with the catalyst pyridine under reflux. The reaction yielded a white crystalline substance that was purified and chemically characterized as barbarin for use as a Certified Reference Standard or for studies related to equine aminorex identification. Abstract : Synthesis and characterization of barbarin, a naturally occurring compound produced in Brassicaceae plants, that is believed to be related to aminorex positives in the modern sports horse. The compound is now made available as a reference standard.